Influence and countermeasure of specimen misalignment to small-strain behavior of soft marine clay. Issue 2 (17th February 2017) - Ye, Guan-Lin; Wu, Chao-Jun; Wang, Jian-Feng; Wang, Jian-Hua
ABSTRACT: Triaxial test with local displacement transducers is an effective technique to obtain the small-strain stiffness of soils. Many previous studies provided feasible solutions for reducing or avoiding potential sources of error in conventional triaxial tests. However, little literature gave out detailed explanations on how to identify those potential errors from the measured testing data and corresponding solutions. Therefore, nowadays, it is still not easy for a new user to gain proficiency in such kind of advanced tests. In this article, by conducting triaxial tests featured with Hall effect transducer on Shanghai soft marine clay, it is found that the influence of the specimen misalignment to the measured small-strain stiffness cannot be neglected. The typical symptom of specimen misalignment, namely the tilting of specimen, was described carefully. An improved connection between top cap and load cell was applied to overcome the problem. The new connection can reduce the disturbance to specimen in terms of both force and displacement. It can be applied to both isotropic and anisotropic consolidated triaxial tests.